Temporal Structure in Haptic Signaling Under a Cooperative Task - Thorne, Nicolas; Honisch, Juliane J.; Kondo, Toshiyuki; Nasuto, Slawomir; Hayashi, Yoshikatsu (Frontiers in Human Neuroscience, 2019)
Haptic communication between humans plays an important role in society. Although this form of communication is ubiquitous at all levels of society and of human development, little is known about how synchronized coordination of motion between two persons would lead to higher-order cognitive functions used in communication. In this study, we developed a novel experimental paradigm of a coin-collecting task in which participants used their hands to control the rod to collect the coins on the screen. We characterized the haptic interactions between the paired participants, while paired participants were taking part in a cooperative task. The individual participants first completed this task on their own, and then, with the partner randomly assigned for the cooperative task. % Single participant experiments were used as a baseline to compare results of the paired participants. Forces applied to the rod were translated to four possible haptic states which encode the combination of the haptic interactions. % As a next step, pairs of consecutive haptic states were then combined into 16 possible haptic signals which were classified in terms of their temporal patterns using a Tsallis q-exponential function. % For paired participants, 80% of the haptic signals could be fit by the Tsallis q-exponential. On the other hand, only 30% of the signals found in the single participant trials could be fit by the Tsallis q-exponential. This shows a clear difference in the temporal structures of haptic signals when participants are interacting with each other and when they are not. % We also found a large difference in the number of haptic signals used by paired participants and singles. Single participants only used 1/4 of the possible haptic signals. Pairs on the other hand, used more than half of the possible signals. % These results suggest that temporal structures present in haptic communication could be the linked to the emergence of language at an evolutionary level.